Microstructure and opto-electrical properties of SnO2:In2O3 alloys thin films prepared by ultrasonic spray. (1st January 2013) - Ynineb, Fayssal; Hafdallah, Abdelkader; Attaf, Nadhir; Aida, Mohammed Salah; Bougdira, Jamal; Rinnert, Hervé
In this work, we study the effect of indium weight ratio in solution: R = [In/Sn] on the properties of SnO2 :In2 O3 thin films prepared by ultrasonic spray method at fixed temperature of 300°C. The used precursors are tin chloride dehydrate and indium trichloride dissolved in methanol. To prepare hybrid SnO2 :In2 O3 thin films with different concentrations, the ratio R is varied in the range of 10–95 wt%. The resulting films were characterised by X-ray diffraction, scanning electron microscopy analysis, UV-visible spectrophotometer and conductivity measurement. The XRD results indicate segregation between SnO2 and In2 O3 phases in all films. The optical transmittance is in the range of [75–85]%. The conductivity values of pure oxides are very low [~10 –3 (Ω.cm) –1 ] and it is increased with R ratio until a maximum value of 1.2 × 10 2 (Ω.cm) –1 obtained at R = 95 wt%. Consequently, the higher figure of merit ( Fm = σ . T . d ) is obtained at this later ratio.